A contação de história na educação infantil: Teatralidade e Educação Somática. - Ana Paula Galdino da Silva (2023)
This research, linked to the Professional Master in Arts program - Prof-Arts, sought to discuss the practice of storytelling in the formation of children in early childhood education, by proposing elements of theater and some principles of somatic education for the classroom under the perspective of its possible creative and pedagogical developments. For this, a theoretical survey of the main assumptions of somatic education was carried out, also investigating the field of theatricality and storytelling. The present study brings a bibliographical survey of the themes of storytelling, somatic education, theatricality, and children's education, addressed in the research, and elaborates a script of experiments thought for the classroom. Based on Slade (1978), Vianna (2005) Souza (2006) Strazzacappa (2001, 2009), Fortin (2010), Dewey (2010), Machado (2010, 2015), Miller (2012, 2016), Santos (2017) and Janiaski (2021), among other theorists, the research sought to understand the possible relationships and complementarities between storytelling, theatricality and principles of somatic education present in pedagogical practice in classroom. Keywords: Art Education; Performing Arts; Theater; Body